The associations of body composition, fitness, and physical activity with balance in children: The Arkansas Active Kids study - Diniz-Sousa, Florêncio; Edwards, Timothy; Diaz, Eva C.; Weber, Judith L.; Børsheim, Elisabet (Gait & posture, 2025)
Balance plays an important role in children's motor development. However, the factors that are associated with balance in children are not yet fully understood. We aimed to investigate the association of body composition, physical fitness, and daily physical activity on balance in children. The sample was composed of 219 children (53 % females), aged 9.0 (IQR = 2.2) years with a body mass index (BMI)-percentile of 74.9 (IQR = 48.7). Balance was evaluated through a force platform in the upright bipedal stance under different sensory conditions. Anthropometry, body composition (dual-energy x-ray absorptiometry), knee maximal strength (isokinetic dynamometer), aerobic capacity (indirect calorimetry), and daily physical activity (accelerometry and questionnaires) were also assessed. Higher levels of body mass, waist circumference, and fat mass were associated with worse balance, whereas greater knee extension strength and peak oxygen uptake were linked to enhanced balance. Among those, fat mass percentage and waist circumference were the most important factors associated with balance performance. Moreover, it was observed that the associations between the identified anthropometric and body composition measures with balance could be counteracted by physical fitness and physical activity levels. Our findings revealed that anthropometric measures, body composition, and physical fitness levels are associated with children's balance. Furthermore, physical fitness and physical activity may be especially relevant, as they could help mitigate the detrimental effect of excess fat mass on postural control. •Higher body mass, waist, and fat mass linked to worse balance; strength and VO2 peak improve it.•Fat mass percentage and waist circumference are key factors in balance performance.•Physical fitness/activity can counterbalance the effects of body composition on stability.